Analisis Kruskal-Wallis Terhadap Hubungan Antara Gangguan Tidur Dengan Kualitas Tidur - Witri Wardani Hulu; Yuni Sarah Siregar; Nurul Khairunnisa; Sisti Nadia Amali (PT. Sharia Journal and Education Center, 2024)
Sleep disorders are a global health issue that significantly impact an individual's sleep quality, encompassing physical, mental, and social aspects. This study aims to analyze the relationship between types of sleep disorders, such as insomnia and sleep apnea, and sleep quality using the Kruskal-Wallis test. This method was chosen for its ability to analyze non-normally distributed data and compare median differences across independent groups. The research data was derived from secondary datasets, and the analysis revealed significant differences in sleep quality between groups without sleep disorders and those with insomnia. However, no significant differences were found between the insomnia and sleep apnea groups. A post-hoc analysis with Bonferroni correction supported these findings, indicating that insomnia has a more detrimental impact on sleep quality than sleep apnea. This study provides new insights into the effects of sleep disorders on sleep quality and serves as a foundation for developing interventions to improve sleep quality in individuals with sleep disorders.